Männyntaimilla juuret kasvavat syksyllä pitempään kuin verso - Poteri, Marja (Metsäntutkimuslaitos, 2001)
Selostus artikkelista: Iivonen, Sari, Rikala, Risto ja Vapaavuori, Elina. 2001. Seasonal root growth of Scots pine seedlings in relation to shoot phenology, carbohydrate status, and nutrient supply. Canadian Journal of Forest Research 31: 1569–1578.
Julkaisusatoa